Sequestration of Voriconazole and Vancomycin Into Contemporary Extracorporeal Membrane Oxygenation Circuits: An in vitro Study - Raffaeli, Genny; Cavallaro, Giacomo; Allegaert, Karel; Koch, Birgit C. P.; Mosca, Fabio; Tibboel, Dick; Wildschut, Enno D. (Frontiers in Pediatrics, 2020)
Background: Bacterial and fungal infections are common and often contribute to death in patients undergoing extracorporeal membrane oxygenation (ECMO). Drug disposition is altered during ECMO, and adsorption in the circuit is an established causative factor. Vancomycin and voriconazole are widely used, despite the lack of evidence-based prescription guidelines. Objective: To determine the extraction of voriconazole and vancomycin by the Xenios/Novalung ECMO circuits. Methods: We have set-up nine closed-loop ECMO circuits, consisting of four different iLA Activve® kits for neonatal, pediatric and adult support: three iLA-Activve MiniLung® petite kits, two iLA-Activve MiniLung® kits, two iLA-Activve iLA® kits and two iLA-Activve X-lung® kits. The circuits were primed with whole blood and maintained at physiologic conditions for 24 hours. Voriconazole and vancomycin were injected as a single-bolus age-related dose into the circuits. Pre-membrane (P2) blood samples were obtained at baseline and after drug injection at 2, 10, 30, 180, 360 minutes, and at 24 hours. A control sample at 2 minutes was collected for spontaneous drug degradation testing at 24 hours. Results: 72 samples were analyzed in triplicate. The mean percentage of drug recovery at 24 hours was 20% for voriconazole and 62% for vancomycin. Conclusions: The extraction of voriconazole and vancomycin by contemporary ECMO circuits is clinically relevant across all age-related circuit sizes and may result in reduced drug exposure in vivo.